TRIP GENERATION AND PARKING DEMAND FOR ONE MIXED ACTIVITY COMMERCIAL CENTER - Subarnowo (NIM 26994010), Bagas
ABSTRACT: This thesis observes vehicle trips and parking demand characteristic in mixed land use. The main objectives of the thesis are: a) to study the characteristics of vehicle trips and parking in a business area with mixed land-use; b)to derive estimates for vehicle trip rates and parking demand for the mixed land-use. Data were collected from one mixed land use area, with the following characteristics: The existing land use in the location has multi activities, i.e., offices, books stores, bank, theatres, restaurant, food service, furniture, clinic and others, All visitors who have cars share the same parking area. The location has an exclusive parking area. The survey site was located in mixed land use at Pondok Gede Asri a shopping center in the vicinity of East Jakarta. A number of surveys were undertaken to obtain profiles of trip arrival rates and parking accumulation. The surveys consisted of parking counts, interviews of business employees, interview of visitors, interviews of employees, interviews of theatre visitors, and a population count. From interview surveys taken before and after shopping, it was found that the percentage of multi purpose trips was 15.4% before and 25.4% after; for the theatre visitors it was 100% before and 43% after. The results of the study show that 14.3% of visitors used a private car and 59.1% came by public transport. Parking turnover per space was 6.94 for car and 7.76 for motor cycles. (This indicates normally distributed arrivals and departures and short parking durations). The mode of parking duration for cars was 45 minutes and the mean was 105 minutes. For motor cycles, the mode was 30 minutes and the mean was 83 minutes. The parking utilization ratio of cars at time period 11:00 to 12:00 hours was 1.11 and 0.98 for motor cycles. Daily vehicle trip rate per day for cars was found to be 14.6 daily car trips per 100 square meters of occupied gross leasable area (GLA) and 8.2 for motor cycles. The parking demand at the mixed land use shopping centre with a supply of 400 car parking spaces was examined on a peak demand day. The peak demand exceeded the supply by 10.75 %. The parking rate for cars was found to be 2.34 spaces per 100 square meters of GLA. For motor cycle with a supply of 200 motor cycle parking spaces, the peak demand was found less than the supply. The parking rate for motor cycle was found to be 1.03 motor cycle spaces per 100 square meters of GLA.